High occurrence of Cryptosporidium ubiquitum and Giardia duodenalis genotype E in sheep from Brazil - Paz e Silva, Flavio Medeiros [UNESP]; Lopes, Raimundo Souza [UNESP]; Saraiva Bresciani, Katia Denise [UNESP]; Talamini Amarante, Alessandro Francisco [UNESP]; Araujo, Joao Pessoa [UNESP] (Versita, 2014)
In this paper we report the occurrence of zoonotic species of Cryptosporidium (C. ubiquitum and C. parvum subtype IIaA15G2R1) and the host-specific Giardia duodenalis genotype E in a sheep farm from Brazil. Fecal specimens were collected from 100 animals and screened for the presence of G. duodenalis and Cryptosporidium spp. by enzyme immunoassay (EIA) and polymerase chain reaction (PCR). Restriction fragment length polymorphism (RFLP) and sequence analysis of selected samples was used to confirm the species and to characterize the isolates. Of 100 specimens, 34 were positive for Giardia (34%) and 25 were positive for Cryptosporidium (25%). The prevalence of Giardia and Cryptosporidium was higher in lambs than in ewes. Co-infection was observed in 14% of animals. All G. duodenalis isolates belonged to genotype E. The genetic characterization performed in 22 Cryptosporidium-positive samples revealed the presence of zoonotic C. ubiquitum and C. parvum in 76% (19/25) and 12% (3/25) of infected animals, respectively. The presence of zoonotic Cryptosporidium subtypes in lambs was of epidemiological and public health relevance.
Keywords: Cryptosporidium; Giardia; genotypes; sheep; zoonosis